PERAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. PERTAMINA HULU ENERGY WMO DALAM PENGEMBANGAN MASYARAKAT DI KECAMATAN GRESIK - AGUSTINA, NIKE (Jurnal Akuntansi AKUNESA, 2012)
PT. Pertamina Hulu Energy WMO is a pure oil-producing companies that operate in the district of Gresik. The existence of social responsibility to the community around the area holding company with community development programs. The Community development programs include improving the quality of education, increase small and medium businesses, improving the quality of health, environmental conservation, and improvement of public facilities. The impact of community development programs covering is an increase in assets, the expansion of business networks, develop the labor market, as well as skill development. Keywords: Corporate Social Responsbility, community development programs, the role of CSR, CSR impact.